A comparative study of female identity construction in Chinese and American advertisements. (25th November 2019) - Mao, Yansheng; Hwuang, Ximin
Abstract : This article investigates the issue of female identity construction in Chinese and in American advertisements from a contrastive perspective rarely adopted in the related literature. We have found that, while the identity of women constructed in the Chinese advertisements reflects the traditional expectations of women, such as being beauty-conscious, romance-pursuing, and maternal love-representing, the identities of women found in the American advertisements are those of confidence and uniqueness. Our interview data indicate that these findings are reflections of respective cultural values in the two societies. That is, women in Chinese culture are still seen as being traditional whereas women in the United States are seen as independent and goal-driven.